Estudo sobre as distorções causadas por manobras em bancos de capacitores nos sistemas elétricos de potência - Melo, Mateus Ferreira (Universidade Federal Rural do Semi-Árido, 2021)
With the importance of capacitor bank installations in electrical systems, to correct your power factor, It is essential to carry out an analysis of the impact of installing this equipment on the network, in view of the emergence of disturbances that can damage other existing equipment on the network. This work makes a study by analysis of current and voltage, so that it can be visualized how these disturbances that are caused in the switching of capacitor banks behave, both in the installation and closing of fuse switches, as well as in the withdrawal of these banks due to the opening of the keys. To carry out this study, the ATPDraw software is used, where it is possible to perform a system modeling and perform simulations that represent these switches, one for opening and one for closing. Finally, it is possible to obtain the results of these simulations through plotted graphics where voltage and current are analyzed by the software itself, checking the impacts caused due to these maneuvering transients
Keywords: Banco de Capacitores; Transitórios de Energia; ATPDraw; Sistema Elétrico de Potência; Capacitors bank; Energy Transients; ATPDraw; Electric Power System; ENGENHARIAS::ENGENHARIA ELETRICA